2006
DOI: 10.1242/jcs.02973
|View full text |Cite
|
Sign up to set email alerts
|

Wingless signaling modulates cadherin-mediated cell adhesion inDrosophilaimaginal disc cells

Abstract: Armadillo, the Drosophila homolog of β-catenin, plays a crucial role in both the Wingless signal transduction pathway and cadherin-mediated cell-cell adhesion, raising the possibility that Wg signaling affects cell adhesion. Here, we use a tissue culture system that allows conditional activation of the Wingless signaling pathway and modulation of E-cadherin expression levels. We show that activation of the Wingless signaling pathway leads to the accumulation of hypophosphorylated Armadillo in the cytoplasm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…They further reported that DE-cad overexpression clones apically constricted, suggesting a causal relationship between Wnt pathway activation, elevated DE-cad, and apical constriction (Jaiswal et al, 2006). Others have also reported that DE-cad is a transcriptional target of Wnt signaling (Wodarz et al, 2006). Together, this suggested that at least some of the APC null morphological changes could be due to Wnt-mediated upregulation of DE-cad .…”
Section: Resultsmentioning
confidence: 99%
“…They further reported that DE-cad overexpression clones apically constricted, suggesting a causal relationship between Wnt pathway activation, elevated DE-cad, and apical constriction (Jaiswal et al, 2006). Others have also reported that DE-cad is a transcriptional target of Wnt signaling (Wodarz et al, 2006). Together, this suggested that at least some of the APC null morphological changes could be due to Wnt-mediated upregulation of DE-cad .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in addition to reports of Wnt pathway activation having effects on cadherin function (Bradley et al 1993;Hinck et al 1994b;Hinck et al 1994a;Yanagawa et al 1997;Shariatmadari et al 2005;Ulrich et al 2005;Wodarz et al 2006), there are indications of physical associations between Wnt and cadherin/protocadherin pathway components Qin et al 2005;Hay et al 2009), suggesting that cadherins are likely to modulate canonical (b-catenin mediated) or noncanonical (alternative) Wnt pathways.…”
Section: P120 Subfamilymentioning
confidence: 99%
“…Furthermore, release of Arm from the AJs, and its stabilization, may also contribute to the activation of Arm. The stimulation of E-cadherin transcription by Src42A may be a direct consequence of Arm activation, as stimulation of E-cadherin synthesis by Wg was observed in cultured Drosophila cells (Wodarz et al, 2006). TCF-dependent synthesis of E-cadherin by itself was not rate limiting for tracheal cell adhesion, probably because its absence left the level of E-cadherin above the threshold to maintain cell adhesion.…”
mentioning
confidence: 97%